Existence of waves for a reaction–diffusion–dispersion system. (March 2019) - Sen, M.; Volpert, V.; Vougalter, V.
Abstract: Existence of travelling waves is studied for a bistable reaction–diffusion system of equations with linear integral terms (dispersion) and with some conditions on the nonlinearity. The proof is based on the Leray–Schauder method using the topological degree theory for Fredholm and proper operators with the zero index and a priori estimates of solutions in properly chosen weighted spaces.